Effects of brassinosteroid on cotton regeneration via somatic embryogenesis - AYDİN, YILDIZ (SPRINGER, 2006)
Brassinolide (BR), which is the most biologically active brassinosteroid, was used to examine the potential effect of hormone on cotton somatic embryogenesis. Ten-day-old cotton (Gossypium hirsutum L, cv. Cooker) seedlings were used for explant source and hypocotyls were removed and cultured on MS basal medium with 135 vitamins supplemented with 1 mg/L 6-benzylaminopurine + 0.5 mg/L kinetin for callus induction. After one month proliferating calli pieces were collected and cultured on MS basal medium containing various concentrations of BR (0.1, 0.5, 1.0 AM) with their controls. BR treatments were negatively effective on the fresh weight of calli when compared to control. Differential somatic embryogenesis maturation rates due to BR treatment were observed. Somatic embryogenesis was stimulated especially for transition to cotyledonary phase at 0.5 mg/L BR. Histological preparations from embryogenic calli and somatic embryos at different stages of development revealed the spontaneous polyploidisation during early somatic embryogenesis on BR-treated calli. Present results suggest that BR negatively effected calli growth, however, had a stimulating role in maturation of somatic embryos.
Keywords: Gossypium hirsutum L.; somatic embryogenesis; brassinolide; polyploidy; calli growth; PLANT-REGENERATION; GROWTH